Evaluation of C/N Ratio in Spirulina platensis Cultivation using Molasses Addition as Organic Carbon Source - Tutik Muji Setyoningrum; Viska A.W.; Annisaturraihan A; N Islamy Putra; Muhamad Maulana Azimatun Nur (Eksergi)
Growth of Spirulina platensis requiers nitrogen, phosphate, and carbon. Urea is used as source of nitrogen, TSP as source of phosphate, and sodium bicarbonate (NaHCO3) as source of carbon.  The purpose of this research was to evaluate C:N ratio of medium using different concentration of molase and urea addition as replacement of commercial medium. Spirulina platensis was cultivated  as a control consist of 1500 ppm NaHCO3 as source of carbon, 80 ppm urea as source oh nitrogen, 20 ppm TSP (Triple Super Phosphate) as source of phosphate, 1 ppm FeCl3 and 50 µg/l B12 vitamin as source of micronutrients. Spirulina platensis was cultivated in 2-liter of erlenmeyer flask with variation composition of urea and molasses in growth media by adding 20% (w/w) control medium. Urea was varied between 0; 16; and 80 mg L-1, molasses was varied at the level of 0,1-0,9 g L-1. Cultivation was maintained in pH 9-10, light intensity 6000-7000 lux and 280C. Mini aerator pump is used as a medium stirrer. The best result were obtained at the medium varied of 0,1 g L-1 and 16 ppm of urea with growth rate of  0.230 day-1 , C:N ratio 6.8, and dry biomass of 0.333 g L-1.